A Needs Assessment of Brain Death Education in Pediatric Critical Care Medicine Fellowships*. Issue 7 (July 2018) - Ausmus, Andrew M.; Simpson, Pippa M.; Zhang, Liyun; Petersen, Tara L.
Abstract : Objectives: To assess the current training in brain death examination provided during pediatric critical care medicine fellowship. Design: Internet-based survey. Setting: United States pediatric critical care medicine fellowship programs. Subjects: Sixty-four pediatric critical care medicine fellowship program directors and 230 current pediatric critical care medicine fellows/recent graduates were invited to participate. Interventions: Participants were asked demographic questions related to their fellowship programs, training currently provided at their fellowship programs, previous experience with brain death examinations (fellows/graduates), and perceptions regarding the adequacy of current training. Measurements and Main Results: Twenty-nine program directors (45%) and 91 current fellows/graduates (40%) responded. Third-year fellows reported having performed a median of five examinations (interquartile range, 3–6). On a five-point Likert scale, 93% of program directors responded they "agree" or "strongly agree" that their fellows receive enough instruction on performing brain death examinations compared with 67% of fellows and graduates ( p = 0.007). The responses were similar when asked about opportunity to practice brain death examinations (90% vs 54%; p < 0.001). In a regression tree analysis, number of brain death examinations performed was the strongest predictor of trainee satisfaction. Both fellows and program directors preferred bedside demonstration or simulation as educational modalities to add to the fellowship curriculum. Conclusions: Pediatric critical care medicine fellows overall perform relatively few brain death examinations during their training. Pediatric critical care medicine fellows and program directors disagree in their perceptions of the current training in brain death examination, with fellows perceiving a need for increased training. Both program directors and fellows prefer additional training using bedside demonstration or simulation. Since clinical exposure to brain death examinations is variable, adding simulated brain death examinations to the pediatric critical care medicine fellowship curriculum could help standardize the experience.